Identity Crisis in Desai’s the Inheritance of Loss - Ammai, Narayan Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The Inheritance of Loss by Kiran Desai is a novel set in 1980s which deals with the theme of identity crisis especially of the Judge, the Cook, Sai, Biju and Gyan who struggle with their identity within their own nation and foreign land and fail to maintain a strong position even within their own community due to the effect of modernization and globalization. These lower ranked people are victimized from elite class in search of identity. Desai depicts how minority group’s identity is excluded, back grounded and suppressed by the so-called majority group in literature through the discourse. She has also shown how world’s globalized context has exploited and dominated the working-class people’s identity and freedom. This study focuses on exploring the complex web of relationships between identity and discourse as well as investigating the significant roles of literature in the construction of identity. The question that it arises is how identity is shaped by discourse in literature. In order to answer this question a wholesale analysis of the text is carried out in light of Tope Omoniyi’s Discourse and identity, James Paul Gee’s Critical Discourse Analysis and Stuart Hall’s Cultural Identity and Diaspora.